Spatial Distribution of Mucilage in the Rhizosphere Measured With Infrared Spectroscopy - Holz, Maire; Leue, Martin; Ahmed, Mutez A.; Benard, Pascal; Gerke, Horst H.; Carminati, Andrea (Frontiers in Environmental Science, 2018)
Mucilage is receiving increasing attention because of its putative effects on plant growth, but so far no method is available to measure its spatial distribution in the rhizosphere. We tested whether the C-H signal related to mucilage fatty acids is detectable by infrared spectroscopy and if this method can be used to determine the spatial distribution of mucilage in the rhizosphere. Maize plants were grown in rhizoboxes filled with soil free of organic matter. Infrared measurements were carried out along transects perpendicular as well as axially to the root channels. The perpendicular profiles of gradients of the C-H proportions showed a decrease of C-H with increasing distance: 0.8 mm apart from the root center the C-H signals achieved a level near zero. The measured concentrations of mucilage were comparable with results obtained in previous studies, which encourages the use of infrared spectroscopy to quantitatively image mucilage in the rhizosphere.